2009 IEEE International Conference on Robotics and Automation 2009
DOI: 10.1109/robot.2009.5152791
|View full text |Cite
|
Sign up to set email alerts
|

Global transparency analysis of the Lawrence teleoperator architecture

Abstract: Despite the frequent use of the Lawrence architecture since its introduction in the early 90's, its global transparency characteristics have not yet been fully analyzed. That is the goal of this paper. We state and prove necessary and sufficient conditions for transparency, with special attention to the information sent across the communication layer. In particular, it is shown that transparency can be preserved even though one, and even two, communication channels are set to zero. The results may serve as a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…The forward flow haptic control is a control scheme where velocity is sent from the master to the slave and force from the slave to the master (Naerum and Hannaford, 2009). The full development of haptic control for our system is described in Fjellin (2013).…”
Section: Forward Flow Haptic Controlmentioning
confidence: 99%
“…The forward flow haptic control is a control scheme where velocity is sent from the master to the slave and force from the slave to the master (Naerum and Hannaford, 2009). The full development of haptic control for our system is described in Fjellin (2013).…”
Section: Forward Flow Haptic Controlmentioning
confidence: 99%
“…In theory, full transparency can also be obtained with a three-channel controller [7] and a two-channel controller [8], again under the assumption of ideal conditions. In literature, a lot of attention has been paid to both the transparency properties of the extended Lawrence Architecture [7], [9], [8], [10] and to the stability properties. The detailed stability analysis in [11], [12], [1], however, are restricted to two-channel controllers, while the analyses in [5], [6], [13] are very general.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is relatively easy to delineate a range of stiffnesses [0, K max e ] with which the surgeon typically interacts. Here, the Bounded Environment Passivity method is used to study the stability properties of a 3-channel controller originating from the Extended Lawrence Architecture [10]. Compared to the Position-Force controller studied in [1], this 3-channel controller has more interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Salcudean et al (2000) applied the four channel control algorithm to systems under rate control. Tavakoli et al (2007) analyzes the stability properties of a discrete implementation of the four channel controller and Naerum and Hannaford (2009) analyzes the global transparency properties of all possible forms of this control architecture. Hashtrudi-Zaad and Salcudean (1999) showed that perfect transparency could also be obtained with three instead of four channels.…”
Section: Bilateral Controlmentioning
confidence: 99%